STRATEGI BERTAHAN HIDDUP KELUARGA TERDAMPAK BANJIR PERUMAHAN MUTIARA WITAYU KECAMATAN RUMBAI - Rio Indra Silitonga; Rina Susanti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This research was carried out in Sri Meranti Rumbai Village, around the Witayu residential area, Pekanbaru-Riau City. Flood cases are an annual agenda that hit the city of Pekanbaru, especially the Siak Riverside area, Sri Meranti Rumbai Village. The activities carried out by the community when the flood hit was to survive in a flood situation to protect people's property, there were also those who fled to survive in refugee posts provided by various community institutions. This is, people who live in flood situations have 3 types of strategies in dealing with the impact of floods (1) Active strategy, is an adaptation by allocating the ability to survive in flood situations (2) Passive strategy, namely the efforts of flood victims to save expenses in meeting the economic needs of the family (3) Network Strategy, namely, adapting by utilizing assistance from various parties who care about flood victims from the government and non-government (private) sectors. Floods that have an impact on the community greatly affect the economic needs of the family and also have an impact on health, which tends to attack when a flood disaster hits flood-prone areas, especially the siak riverside area, Sri Meranti Rumbai village. Keywords: Flood, Flood Impact, Active Strategy, Passive Strategy and Network Strategy